Regimes of Extreme Permission in Southeast Asia: theorizing State-Corporate Crime in the Global South - Ciocchini, Pablo Leandro (The British journal of criminology, 2023)
Corporations’ profit-making objectives are a central force guiding development strategies in the Global South but contradictorily can be blamed for a range of social and environmental harms. This article brings a state-corporate crime lens to bear on the economic and political processes that shape Global South-located commodity production. It seeks to understand the functioning of neo-imperialist profiteering through elaborating the concept of regimes of extreme permission, described as modalities of ‘intense’ accumulation, defined by weaker or unstable forms of hegemony consolidation, illegal/illicit practices, state-sanctioned violence and various socio-environmental degradations. Through analyses of two regimes of extreme permission in the SE Asian context—Indonesian palm oil plantations and Export Processing Zones for garment production in the Greater Mekong Subregion—the paper describes the role of states and corporations in constructing the repressive socio-political space required for neo-colonial corporate accumulation. We contribute to ‘Southernizing’ criminology by re-articulating state-corporate crime theory within imperialist contexts. It also shows that neo-colonialism can be understood as the de-regulation of corporate accumulation.